Pseudotumor in the temporomandibular joint: A case report. (2015) - Yoshitake, Hiroyuki; Kayamori, Kou; Nakamura, Ryosuke; Wake, Sou; Harada, Kiyoshi
Highlights: Neoplastic disease of the TMJ is a rare condition. We report a case of pseudotumor of the TMJ. This case was difficult to differentiate from synovial chondromatosis. Abstract: Introduction: Neoplastic disease in the temporomandibular joint (TMJ) is a rare condition and is difficult to differentiate from temporomandibular disorders (TMD) based on symptoms and simple X-ray examinations. Potential differential diagnoses include synovial chondromatosis and pseudotumor, both of which are also relatively rare in the TMJ. Presentation of case: We report a case of pseudotumor of the TMJ that was difficult to differentiate from synovial chondromatosis in a 71-year-old woman with a chief complaint of pain in the left TMJ. MRI of the right TMJ initially led to diagnosis of synovial chondromatosis. Extirpation of the lesion was performed under general anesthesia. Histopathological findings of the resected specimen revealed inflammatory granulation tissue without cellular atypism. Discussion: The pathological findings for the resected specimen were compatible with pseudotumor of the TMJ. These findings were not supportive of synovial chondromatosis or other tumor diseases. Conclusion: This case illustrates the importance of careful examination of a mass lesion in the TMJ for differentiation from other TMJ-related diseases.